Weight Gain After Heart Transplantation in Adults: Systematic Review and Meta-Analysis. Issue 9 (20th September 2021) - Miura, Kyoko; Yu, Regina; Sivapalan, Krishnaa; Liyanage, Upekha E.; Entwistle, Timothy; McKenzie, Scott C.; Green, Adèle C.
Abstract : Gain in weight is common after heart transplantation but the magnitude of usual weight gain and whether this varies by country is unknown. We systematically reviewed all relevant studies to quantify weight change among heart transplant recipients (HTRs) in the years after transplantation and assess variation with geographic location. We searched PubMed, Cumulative Index to Nursing and Allied Health Literature, and Excerpta Medica Database databases to September 2020. Eligible studies reported adult HTRs' mean/median weight and/or body mass index (BMI) up to time of transplantation (baseline) and posttransplantation in any language. Weighted mean differences (WMDs) (95% confidence intervals [CIs]) of weight/BMI from baseline to posttransplantation were estimated using a random-effects model. Ten studies met the inclusion criteria. Pooled analysis showed weight gain of 7.1 kg (95% CI, 4.4–9.8 kg) in HTRs 12 months posttransplant, with corresponding BMI increase of 1.69 kg/m 2 (95% CI, 0.83–2.55 kg/m 2 ). Greatest weight gain at 12 months posttransplant occurred in US HTRs (WMD weight 10.42 kg, BMI 3.25 kg/m 2 ) and least, in European HTRs (WMD weight 3.10 kg, BMI 0.78 kg/m 2 ). In conclusion, HTRs gain substantial weight in the years after transplantation, but varying widely by geographic location.